Analisis Kelelahan Dan Kejenuhan Karyawan Pada Kantor Pegadaian Cabang Tenggarong - Nicky Nur, Muhammad; Iskandar, Iskandar; Erwinsyah, Erwinsyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
The aim of this research is to find out and examine the main factors causing employee burnout at the Tenggarong branch of the Pegadaian Office. The sample in this study was 28 employees at the Tenggarong pawnshop office. The sampling technique as a whole without exception, the analytical tool used is descriptive statistics. Based on the results of research conducted using the Maslch Burnout Inventory measuring instrument (MBI) which consists of three indicators, namely emotional exhaustion, depersonalization, and lack of self-actualization. The research results show that the emotional exhaustion indicator has a value of 2.257, the depersonalization indicator has a value of 2.011, and lack of self-actualization has a value of 2.15. It can be concluded that the main cause of employee burnout or exhaustion is an indicator of emotional exhaustion. Because it has quite high values ​​from all indicators.